2019
DOI: 10.4236/jbise.2019.127026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ozone Carried by Liposomes in the Therapy of Infectious and Skin-Regenerating Ocular Surface

Abstract: Effect of the ozonated oil in liposomes: they act against Staphylococcus aureus and Pseudomonas aeruginosa is among the most frequent eye pathogens and causes acute and chronic infections of the ocular surface. Staphylococcus aureus and Pseudomonas aeruginosa were tested in this study. The bacterial suspension of Staphylococcus aureus was diluted to obtain 150 CFU/ml. The bacterial suspension of Pseudomonas aeruginosa was diluted to obtain 15 CFU/ml. Various volumes of liposome-vehiculated ozonated oil were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…aureus and P . aeruginosa was observed by Cutarelli et al [ 18 ]. Serio et al [ 19 ] confirmed the antibacterial activity of ozonated sunflower seed oil (Oz.Or.Oil 30) against both Gram-negative ( E .…”
Section: Discussionmentioning
confidence: 92%
“…aureus and P . aeruginosa was observed by Cutarelli et al [ 18 ]. Serio et al [ 19 ] confirmed the antibacterial activity of ozonated sunflower seed oil (Oz.Or.Oil 30) against both Gram-negative ( E .…”
Section: Discussionmentioning
confidence: 92%
“…More recently, the cytotoxicity of liposome-vehiculated ozonated oil against S. aureus and P. aeruginosa, which are among the most frequent eye pathogens, has been analyzed [100]. The microbiological results clearly show antimicrobial efficacy and there was no evidence of any toxicity against keratinocytes.…”
Section: Macro- Micro- and Nanoencapsulation Of Oilsmentioning
confidence: 99%
“…The introduction of oxidizing agents in drops for disinfection of the ocular surface is very recent. Their use has been advocated on the basis of efficacy against all microorganisms, as well as the lack of induction of antibiotic resistance [13]. The ozonated…”
Section: Introductionmentioning
confidence: 99%